Pendampingan Manajemen Pengelolaan BUMDes untuk Meningkatkan Kesejahteraan dan Pengembangan Ekonomi Lokal di Desa Purworejo - Salman Al Farisi; Sami’an Sami’an; Sri Puji Ningsih; M. Fatkhul Ibad; Muhammad Syakif Arsilan; Nadinil Hasna (Pusat Riset dan Inovasi Nasional, 2025)
Village-Owned Enterprises (BUMDes) are institutions managed by village communities that operate in the field of village economic resources, with the aim of maximizing village assets. BUMDes can directly foster business opportunities, create employment, and increase village income. Villages can become self-reliant and capable of alleviating poverty by improving community welfare—provided that BUMDes are managed properly, effectively, and efficiently. However, there is still a low level of knowledge regarding the management of business organizations developed by BUMDes. Due to this condition, BUMDes have not yet functioned optimally as a source of economic growth for the organization itself, let alone for the wider community. Providing management training and developing professional human resources to manage BUMDes effectively is essential. This includes the management of BUMDes administrative governance, understanding relevant regulations and legal frameworks, and improving the economy and welfare through the buying and selling of local products, especially those produced by village rice farmers.